2015
DOI: 10.1137/140988966
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamics of Three-Dimensional Vesicles: A Numerical Approach

Abstract: A three-dimensional numerical model of vesicle electrohydrodynamics in the presence of DC electric fields is presented. The vesicle membrane is modeled as a thin capacitive interface through the use of a semi-implicit level set Jet scheme. The enclosed volume and surface area are conserved both locally and globally by a new Navier-Stokes projection method. The electric field calculations explicitly take into account the capacitive interface by an implicit Immersed Interface Method formulation, which calculates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 74 publications
3
38
0
Order By: Relevance
“…The flow field with variable fluid properties is computed using a continuum surface force method [29]. In such a method the singular interface forces are extended into the embedding domain via a smoothed Dirac delta function and discontinuous fluid properties are taken to vary smoothly from one domain to another.…”
Section: Methodsmentioning
confidence: 99%
“…The flow field with variable fluid properties is computed using a continuum surface force method [29]. In such a method the singular interface forces are extended into the embedding domain via a smoothed Dirac delta function and discontinuous fluid properties are taken to vary smoothly from one domain to another.…”
Section: Methodsmentioning
confidence: 99%
“…In an intermediate dynamic, called breathing or trembling, vesicles have large periodic deformations while also undergoing a tumbling like dynamic. Recent theoretical work has demonstrated that the application of a DC electric field can be used to disrupt this behavior [16]. Knowledge about the influence of controllable fields on the dynamics of vesicles in externally driven fluid flows is crucial to advance vesicle-based technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Complete details of the method including convergence study can be found in Kolahdouz et al. [17]. For more details on the algorithm used to couple the system, readers are referred to Gera et al [30].…”
Section: E Numerical Methodsmentioning
confidence: 99%